Study of the optimization and reduction of the freight account of the company Moinho Paulista S/A – Nita Alimentos - Oliveira, Elizângela de Jesus; Andrade, Darly Fernando; Almeida, Larissa Farias (Brazilian Journal of Production Engineering, 2020)
This study addresses the topic of cargo optimization in order to reduce freight costs, in view of a project that aims to facilitate the work of transporting products. The study is justified by the relevance of the theme today, when companies seek their space in the competitive market and want to maximize their results. The general objective of the research is to analyze the process of load optimization as a resource to reduce freight values in the target environment of this research, which has as its specific objectives: to discuss logistics and its role in organizations today; address the importance of technologies in optimizing business results; highlight the volume of cargo as a determining factor for reducing the cost of freight, generating greater profitability. The methodology used was initially based on bibliographic research, later on the case study of the company. In order to achieve the search results. In addition, in this study, the results of the proposal to use a scriptwriter to optimize freight and reduce the cost of this process are discussed.
Keywords: Loads; Optimization; Costs; Profitability